Упростите выражение (x^2+2x+1) + (x^2 - 1)^2=? (a-b)^2 + (a+b)^2=? помгите срочно!

0 голосов
30 просмотров

Упростите выражение (x^2+2x+1) + (x^2 - 1)^2=? (a-b)^2 + (a+b)^2=? помгите срочно!


Алгебра (72 баллов) | 30 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

(x^2+2x+1)+(x-1)^2=x^2+2x+1+\underbrace {x^2-2x+1}_{(x-1)^2}=2(x^2+1)\\\\\\(a-b)^2+(a+b)^2=\underbrace {a^2-2ab+b^2}_{(a-b)^2}+\underbrace {a^2+2ab+b^2}_{(a+b)^2}=2(a^2+b^2)

(835k баллов)
0

хорошо

0

а там же в первом примере

0

во второй

0

скобке

0

там x в квадрате

0

а все я понял

0

дописала пояснения...

0

спасибо

0

нажми оценку

0

нажал